Exploring the educational needs of patients with systemic vasculitis using the educational needs assessment tool. Issue 2 (11th August 2022) - Brolin, Sara; Welin, Elisabet; Lövström, Björn; Bruchfeld, Annette; Gunnarsson, Iva; Pettersson, Susanne
Abstract: Objectives: Knowledge and health literacy enable patients to monitor symptoms and disease impact. Educational needs have previously been explored in rheumatology, but scarcely for patients with ANCA-associated vasculitis (AAV). The aim of the study was to assess the educational needs among patients with AAV using the educational needs assessment tool (ENAT). Methods: This was a cross-sectional observational study including adults with AAV. Educational needs were captured by ENAT. Total ENAT (0–117 points, with higher numbers indicating higher educational need) and the seven domains (managing pain, movement, feelings, disease process, treatment, self-management and support systems) were explored regarding sex, age, education, diagnosis, disease duration and disease activity. To compare domains, a percentage response (0–100%) was calculated. Results: One hundred and seventy-eight individuals (50% men; 34% with disease duration ≤2 years) were included. The total ENAT mean was 66.5 (s .d . 26.6; 57%), with domains as follows: disease process, 78%; self-management, 69%; treatments, 64%; feelings, 56%; managing pain, 48%; support systems, 47%; and movement, 41%. Higher educational needs were found among women in the domains movement, feelings and disease process and in total ENAT (all P < 0.04) compared with men. Higher educational needs were also seen in patients with disease duration ≤2 years regarding disease process, self-management and support systems and in total ENAT compared with patients with longer disease duration (all P < 0.03). Conclusion: This study revealed great educational needs among AAV patients. Some groups expressed higher needs (women and those with shorter disease duration). Increased education for patients with AAV might lead to improved self-care and treatment adherence. Lay Summary: What does this mean for patients ? ANCA-associated vasculitis (AAV) is a rare but potentially life-threatening disease, with high morbidity if left untreated. Patients who receive education on their disease increase their ability to self-monitor potential symptoms. They can recognize early signs and symptoms of relapse, stay compliant with treatment more easily, achieve long-term positive outcomes and prevent increased morbidity. Patients with AAV who are educated regarding medications and potential side effects also report better health-related quality of life. To investigate what type of education is needed among these patients, we used a questionnaire that measures educational needs, the educational needs assessment tool (ENAT). Our aim was to investigate the educational needs in AAV patients with ENAT and to explore whether it differs related to sex, age, education, diagnosis, disease duration and disease activity. The ENAT questionnaire has been used previously in other rheumatic diseases, but not in AAV. We found that 38% of our patients with AAV desired more education, especially on the disease process, self-management and treatment. Women and those with shorter disease duration expressed a greater need for education than men and those with longer disease duration. The ENAT questionnaire has proved useful to help tailor educational efforts for patients with AAV.